1995
DOI: 10.1017/s0252921100037726
|View full text |Cite
|
Sign up to set email alerts
|

Mode Switching in Red Semiregular Variable Stars?

Abstract: Light curve analysis of the carbon variable RY Dra and the oxygen-rich variables TX Dra and AF Cyg is summarised. In each case, two shorter periods were found (which may be connected with the radial pulsation of the stars) and also a long term variation in the mean brightness. In the case of RY Dra, the amplitudes of the shorter periods both decreased while the amplitude of the long secondary variation was found to be increasing. The light curves and frequency spectra of TX Dra and AF Cyg can be interpreted as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 2 publications
(2 reference statements)
0
14
0
Order By: Relevance
“…Mattei (1994) used a period of 280 days in the calculation of predicted maxima for 1994, indicating that a larger period discrepancy was known and measured by 1994 January. The nature of the period change was subsequently investigated independently by Gál & Szatmáry (1995) and Mattei & Foster (1995), who obtained similar results. The most recent published analysis of T UMi was by Szatmáry et al (2003), who interpreted the period variations as arising from a thermal pulse.…”
Section: T Umimentioning
confidence: 92%
See 1 more Smart Citation
“…Mattei (1994) used a period of 280 days in the calculation of predicted maxima for 1994, indicating that a larger period discrepancy was known and measured by 1994 January. The nature of the period change was subsequently investigated independently by Gál & Szatmáry (1995) and Mattei & Foster (1995), who obtained similar results. The most recent published analysis of T UMi was by Szatmáry et al (2003), who interpreted the period variations as arising from a thermal pulse.…”
Section: T Umimentioning
confidence: 92%
“…Since the 1980s work in this field has blossomed; for example, Wood & Zarro (1981) noted that W Dra was a candidate for period changes, Alksne & Alksnis (1985) noted a significant period increase in LX Cyg, and Bateson et al (1988) found the same in BH Cru. The most spectacular case of period change in a Mira star is that of T UMi, described independently by Gál & Szatmáry (1995) and Mattei & Foster (1995). Since then, several surveys and discussions of period change have appeared in the literature, and it is now generally (but not universally) accepted that large period changes are caused by thermal pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Besides a few detections of significant gradual period change (e.g. Gál & Szatmáry 1995;Sterken et al 1999), most of the studies concluded that random period fluctuations dominate the Mira light curves. Interestingly, the amplitude variations remained quite unstudied, likely because of Send offprint requests to: L. L. Kiss, e-mail: l.kiss@physx.u-szeged.hu the nature of the only existing data -low precision visual observations.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, large period variations had been initially observed only in the three Miras R Hya, R Aql and W Dra (Wood & Zarro 1981;hereafter WZ), and these changes were associated with that transitional evolutionary state. Later, large continuous period decreases of around 0.006, 0.004 and 0.003 day/day were founded in T UMi (Gál & Szatmáry 1995), S Sex (Merchán Benítez & Jurado Vargas 2000) and R Cen (Hawkins et al 2001), respectively, which were also interpreted as a possible change in luminosity due to a flash in the helium-burning shell of these objects. All these stars are interesting as test cases for the theoretical models that interpret such period variations as a flash in the helium-burning shell.…”
Section: Discussionmentioning
confidence: 94%
“…Earlier work by Wood & Zarro (1981) had shown that the period changes could be large during certain parts of the helium shell flash cycle, although period variations of this magnitude had been observed in only three Miras (R Hya, R Aql and W Dra). Later, Gál & Szatmáry (1995), Merchán Benítez & Jurado Vargas (2000) and Hawkins et al (2001) found strong period decreases in the Mira stars T UMi, S Sex and R Cen, respectively, which were also interpreted as a change in luminosity due to a flash in the helium-burning shell.…”
Section: Introductionmentioning
confidence: 93%